Regulating microbial agents of human and animal intestinal microbiota: an overview - Pinto, Cristiana da Purificação; Paulo, Elinalva Maciel; Mitoshi, Hélio Kamida; Pinheiro, Carla Santos Ribeiro; Uetanabaro, Ana Paula Trovatti (SITIENTIBUS série Ciências Biológicas, 2007)
Probiotics are alimentary additives constituted by microorganisms that have a beneficial effect in the host. Their main mechanism of action is based on the principle of competitive exclusion. Nowadays several microorganisms have been isolated and selected for the production of probiotic products that are classified by the FDA (Food and Drug Administration) as a GRAS (Generally Recognized Safe) product. There are many probiotics that can be constituted by different species of bacteria, filamentous fungi and yeasts or even by only one microorganism. S. cerevisiae and S. boulardii are the most used yeast species for probiotic production. The administration of these yeasts in the host was reported as safe and well tolerated by children. However, some authors recently described cases of septicemia and fungemy in immunosuppressed and immunocompetent patients that received biotherapy with these yeasts. Thus, this work is a revision of different aspects of the relationship of probiotic microorganisms in human and animal health.